Synthesis and Characterization of Superparamagnetic Iron Oxide-Alginate Hydrogels and Fluid - Kroll, Elizabeth C. (My University, 1996)
Aqueous ferrofluid has been prepared via precipitation of iron oxide into a polysaccharide gel matrix followed by degradation of the polymer to form a stable magnetic colloid. Nanocrystalline particles of iron oxide were formed in an alginate network by the alkaline hydrolysis and oxidation of the crosslinking agent, Fe2+, used to bind the linear polysaccharide chains. Methanol was used to inhibit the degradation of alginate by Fe2+ and oxygen during the precipitation and growth of iron oxide particles. In addition, the structural integrity of the gel was maintained in part by interaction between the iron oxide particulate and the alginate matrix. Controlled chemical degradation of the matrix resulted in a aqueous suspension of alginate-stabilized magnetic iron oxide particles. The resulting fluid is orange-brown in color, optically transparent, superparamagnetic and stable between 2.8<pH<10
The magnetic gels were isolated as 2mm beads containing ~2-20 mmole Fe. X-ray and electron diffraction patterns of the composite correspond to maghemite (γ-Fe2O3) and/or magnetite (Fe3O4). At room temperature, the composite material is superparamagnetic with saturation magnetizations in excess of 20 emu g^-1 at 30kOe. TEM photomicrographs of sectioned beads and of the magnetic fluid revealed the presence of spherical nanocrystalline oxide particles with diameters ranging from 3 nm to 6 nm. The iron oxide-alginate colloid has a diameter of 54nm with an average zeta potential of -51.6 mV.
Keywords: synthesis, characterization, superparamagnetic, iron, oxide-alginate, hydrogels, fluid, polymer, particles, degradation